Iatrogenic Cushing Syndrome due to Application of Potent Topical Corticosteroid: A Case Report (Nepal Journal of Dermatology, Venereology & Leprology, 2019)
Corticosteroids are over the counter and cheaper drugs available in every medical stores in Nepal. Iatrogenic Cushing syndrome due to topical steroids application is a very rare phenomenon in adults.A 32 year female from Janakpur presented with complaints of swelling of face, weight gain, excessive facial hair and fatigue since two years that gradually increased over last one year. She had a past medical history of on and off application of multiple potent topical corticosteroids for disseminated Tinea infection. She was obese with moon facies, buffalo hump and multiple striae over her abdomen. Her blood pressure was raised and her blood sugar was in pre-diabetic range. Laboratory studies were consistent with iatrogenic Cushing syndrome. Patient recovered after discontinuation of topical corticosteroids and treatment with antifungals.Although iatrogenic Cushing syndrome following application of topical corticosteroid is a rare phenomenon in adults, this can happen in a setup like ours where corticosteroids are prescribed as over the counters and patients have very little knowledge about their use. Therefore, we emphasize that patients and pharmacist should be well educated about the consequences of their prolong application and their side effects